Pengaruh Retailing Mix Dan Service Quality Terhadap Kepuasan Konsumen Pada Bolly Sila Kabupaten Bima - Reni Reni; Ismunandar Ismunandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Consumer satisfaction will be formed if it can meet the basic expectations of consumers. Many factors influence consumer satisfaction, including Retailing Mix and Service Quality. The purpose of this research is to determine whether there is an influence of Retailing Mix on customer satisfaction at Bolly Sila Bima Regency, to determine whether there is an effect of Service Quality on customer satisfaction at Bolly Sila Bima Regency and to determine whether there is an effect of Retailing Mix and Service Quality on customer satisfaction at Bolly Sila Bima Regency. The population in this study were consumers of Bolly Sila, Bima Regency, who had shopped at Bolly Sila, Bima Regency. The sample was determined by accidental sampling technique with 60 respondents. The data collection method used was a questionnaire (questionnaire), observation and literature study. Data analysis techniques used in this study were instrument tests (validity test and reliability test), multiple linear regression analysis, T test, f test, correlation coefficient and determination coefficient using the SPSS 20 program. Based on the results of data processing with the T test method, and F test, it is known that the Retailing Mix and Service Quality variables simultaneously have a significant effect on Consumerr Satisfaction at Bolly Sila, Bima Regency. Partially, the results of this study indicate that the Retailing Mix variable has a significant effect on consumer satisfaction at Bolly Sila, Bima Regency. Meanwhile, Service Quality has no significant effect on Consumer Satisfaction at Bolly Sila, Bima Regency.